2013
DOI: 10.1097/phm.0b013e3182a1e6c3
|View full text |Cite
|
Sign up to set email alerts
|

Walking in Water and on Land After an Incomplete Spinal Cord Injury

Abstract: Gait in water of the SCI subjects is associated with kinematic parameters more similar to those of the CTRLs, particularly regarding speed, stride length, and stance phase, supporting the idea that walking in a water environment may be of rehabilitative significance for SCI subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 36 publications
(50 reference statements)
0
22
0
Order By: Relevance
“…After KT treatment, there was better control of balance, as confirmed by the decline in V and L COP parameters (Cortesi et al, 2011; Tamburella et al, 2013a), as well as an improvement in kinematic gait parameters. Decreases in STANCE and DTS reflect improved dynamic postural stability (Tamburella et al, 2013b), which has been suggested to specifically improve gait in subjects with chronic motor incomplete SCI (Tamburella et al, 2013a). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After KT treatment, there was better control of balance, as confirmed by the decline in V and L COP parameters (Cortesi et al, 2011; Tamburella et al, 2013a), as well as an improvement in kinematic gait parameters. Decreases in STANCE and DTS reflect improved dynamic postural stability (Tamburella et al, 2013b), which has been suggested to specifically improve gait in subjects with chronic motor incomplete SCI (Tamburella et al, 2013a). …”
Section: Discussionmentioning
confidence: 99%
“…Locomotion kinematic gait data were recorded and analyzed using the bidimensional KineView Motion System ® (Kineview, Hafnarfjordur, Iceland) per the protocol for chronic SCI subjects in Tamburella et al (2013a,b), based on 3 strides at a self-determined velocity. Spatial movements of the lower extremity segments were monitored, based on the position of passive markers that were placed per the Helen Hayes biomechanical model (Kadaba et al, 1990).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, methods for the collection of quantitative information about movement in UW settings are video-based [7,8,9,10,11]. Cameras positioned above and/or below the level of water acquire images to obtain speed, position, and other biomechanical variables of the anatomical landmarks of interest [12].…”
Section: Introductionmentioning
confidence: 99%
“…Tamburella et al 5 analyze the influence of inwater environment in gait characteristics of subjects with incomplete spinal cord injury and matched healthy controls compared with on-land data. This article reports kinematic data describing the characteristics of walking in an aquatic environment, frequently used in the treatment of gait disorders in spinal cord injury.…”
mentioning
confidence: 99%